2020
DOI: 10.1111/hepr.13567
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for advanced hepatocellular carcinoma based on liver function and portal vein tumor thrombosis

Abstract: Tyrosine kinase inhibitor (TKI) therapy resulted in better prognosis for patients with hepatocellular carcinoma (HCC). However, some cases with Barcelona Clinic Liver Cancer (BCLC) stage C disease still had poor prognosis. This study aimed to investigate prognosis and characteristics of patients with HCC treated with TKI based on liver function and the extent of portal vein tumor thrombosis (PVTT). Methods: Patients receiving TKI therapy (n=345) were recruited retrospectively. Child-Pugh score and albumin-bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The reported ALBI cut‐off value (−2.18) for npRQ (<0.85) was near the border of mALBI 2a and 2b (ALBI score −2.27). A recent study of the efficacy of the predictive value of mALBI divided into four different grades, a more accurate assessment tool for hepatic function than Child‐Pugh class, 34 reported that mALBI grade 1 and 2a indicated better prognosis even in unresectable HCC patients treated with molecular targeting agents 38‐43 . Decline of BTR (≤4.4) was shown to be a prognostic factor in patients with early HCC treated curatively in the present results (HR 1.852, p = 0.005), and the predictive value of ALBI score for low BTR (≤4.4) was −2.588, which was an approximation of cut‐off value of ALBI grade 1, and those of BTR for mALBI grade 2a and 2b were 4.509 (AUC 0.768) and 4.155 (AUC 0.770).…”
Section: Discussionsupporting
confidence: 56%
“…The reported ALBI cut‐off value (−2.18) for npRQ (<0.85) was near the border of mALBI 2a and 2b (ALBI score −2.27). A recent study of the efficacy of the predictive value of mALBI divided into four different grades, a more accurate assessment tool for hepatic function than Child‐Pugh class, 34 reported that mALBI grade 1 and 2a indicated better prognosis even in unresectable HCC patients treated with molecular targeting agents 38‐43 . Decline of BTR (≤4.4) was shown to be a prognostic factor in patients with early HCC treated curatively in the present results (HR 1.852, p = 0.005), and the predictive value of ALBI score for low BTR (≤4.4) was −2.588, which was an approximation of cut‐off value of ALBI grade 1, and those of BTR for mALBI grade 2a and 2b were 4.509 (AUC 0.768) and 4.155 (AUC 0.770).…”
Section: Discussionsupporting
confidence: 56%
“…Some studies about the prognosis of HCC patients with liver function exist, especially regarding ALBI grade and PVTT 10–14 . However, only a few reports about patients with ICC exist, and they mainly focused on surgical cases 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of ICC was based on pathologically proven ICC or on radiologic findings, in accordance with the criteria of practice guidelines and reviews 1,2,9 . The extent of PVTT was classified as follows: Vp0, no PVTT; Vp1, segmental PV invasion; Vp2, right anterior or posterior PV; Vp3, right or left PV; and Vp4, main trunk and/or contralateral portal vein branch to the primarily involved lobe 10–12 . Child–Pugh classification, ALBI, and mALBI grades were used for liver function assessment.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 For unresectable or advanced stage HCC, TACE, and systemic therapy (including targeted/immunotherapy) are major treatment options. 4,6,7 The management and prognosis of HCC largely depend on tumor burden and liver functional reserve. 8 Traditionally, the CTP score, including serum albumin, bilirubin, INR of PT, ascites, and hepatic encephalopathy, are utilized to assess the severity of liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%